Regulating the internal market - Nic Shuibhne, Niamh (Northampton, Mass. : E. Elgar Pub., 2006)
This book explores the management of the internal from market from a legal perspective.
Includes bibliographical references and index.
aug10/05/13
Loans
Keywords: Trade regulation -- European Union countries